Developing a pH-sensitive Al(OH)3 layer-mediated UCNP@Al(OH)3/Au nanohybrid for photothermal therapy and fluorescence imaging in vivo. Issue 47 (19th November 2018) - Chen, Jian; Zhang, Dongya; Zou, Yan; Wang, Zhongjie; Hao, Mingcong; Zheng, Meng; Xue, Xue; Pan, Xiaoxi; Lu, Yiqing; Wang, Jiefei; Shi, Bingyang
Abstract : A pH-responsive and hydrophilic Al(OH)3 mediating layer makes possible the promising integration of photothermal therapy and fluorescence imaging based on upconversion nanoparticles (UCNPs). Abstract : Nanohybrids fabricated with upconversion nanoparticles (UCNPs) and gold nanoparticles (NPs) hold great promise for near-infrared photothermal therapy (NIR-PTT) and upconversion fluorescence imaging. However, the obstacles of poor solubility in water and finite hydrophilic modification method for UCNPs limit their application in biological fields. Herein, we report a novel UCNP@Al(OH)3 /Au nanohybrid mediated by a highly hydrophilic and biocompatible Al(OH)3 layer to realize a synergistic targeted PTT and fluorescence imaging capability to U87MG tumor-bearing mice under NIR light irradiation. The modification with Al(OH)3 layers can improve the water solubility of UCNPs. And cytotoxicity assays and hemolysis assay showed that the modification with Al(OH)3 layers makes UCNPs have low cytotoxicity and good biocompatibility. In addition, the Al(OH)3 layers are thin enough to allow fluorescence resonance energy transfer (FRET) between UCNPs and gold NPs to occur, giving the NPs a good PTT effect for tumor-bearing mice. Meanwhile, as the pH-sensitive Al(OH)3 layers decompose in acidic tumor microenvironments with Au NPs detached from their surface, the FRET effect no longer occurred, subsequently leading to the fluorescence intensity of naked UCNPs being recovered for good imaging effects. The study suggests that Al(OH)3 mediation layer as a promising hydrophilic nanoplatform can potentially be used for the preparation of superior hydrophilic NPs and pH-stimulated drug release carriers for theranostic application in vivo .